The Role of Dormitory Musyrif (Supervisor) in Developing Arabic Speaking Skills at Al-Tibyan Institute - Mhd Firdaus Lubis (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the role of the dormitory musyrif (supervisor) in developing students’ Arabic speaking skills (maharah al-kalam) at Al-Tibyan Institute through daily language practices. The research employed a qualitative approach using a case study design. Data were collected through direct observation of students’ linguistic activities in the dormitory, in-depth interviews with dormitory musyrif (supervisor), teachers, and students, as well as document analysis related to institutional language supervision policies. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, supported by triangulation techniques. The findings reveal that the dormitory musyrif (supervisor) lays a significant role in fostering Arabic language habits, strengthening linguistic discipline, and expanding opportunities for authentic speaking practice in natural settings. The findings show that the development of speaking skill is achieved through key pedagogical mechanisms, namely continuous monitoring, immediate correction, daily practice repetition, and motivational reinforcement, which collectively lead to the formation of stable language habits and promote the natural use of Arabic in daily life. Continuous, comprehensive, and integrated supervision implemented by the dormitory musyrif (supervisor) transforms the dormitory into an effective communicative environment. Therefore, the dormitory musyrif (supervisor) functions as a non-formal pedagogical agent who contributes substantially to the sustainable improvement of students’ Arabic speaking skills.